The Golgi Apparatus and its Next-Door Neighbors - Nakano, Akihiko (Frontiers in Cell and Developmental Biology, 2022)
The Golgi apparatus represents a central compartment of membrane traffic. Its apparent architecture, however, differs considerably among species, from unstacked and scattered cisternae in the budding yeast Saccharomyces cerevisiae to beautiful ministacks in plants and further to gigantic ribbon structures typically seen in mammals. Considering the well-conserved functions of the Golgi, its fundamental structure must have been optimized despite seemingly different architectures. In addition to the core layers of cisternae, the Golgi is usually accompanied by next-door compartments on its cis and trans sides. The trans-Golgi network (TGN) can be now considered as a compartment independent from the Golgi stack. On the cis side, the intermediate compartment between the ER and the Golgi (ERGIC) has been known in mammalian cells, and its functional equivalent is now suggested for yeast and plant cells. High-resolution live imaging is extremely powerful for elucidating the dynamics of these compartments and has revealed amazing similarities in their behaviors, indicating common mechanisms conserved along the long course of evolution. From these new findings, I would like to propose reconsideration of compartments and suggest a new concept to describe their roles comprehensively around the Golgi and in the post-Golgi trafficking.